FSKM repository system e-dissertation module / Nur Mohammad Raqib Kamaruddin - Kamaruddin, Nur Mohammad Raqib (2014)
Dissertation or usually called as thesis is the submitted documentation for a professional qualification presentation of a research that is being rated and judged by professional evaluation panel. It is a requirement as master level students to contribute knowledge in their selected field of research. In Faculty of Computer and Mathematical Sciences of UiTM, dissertation commonly refers to the individual research students where they are studying in the post graduate programmes. The main individual that be the vital part of managing every of the flow in progressing these studies has to taking more of their time to manages the tasks in on time, accurate and efficient in providing the services. As the English proverb says that ‘a drowning man will clutch a straw’, I have invented a web application to simplify the stakeholder to managed the flow of every progressing of all post programme students within short time, accurate and in efficient way. Beside finding the best alternative to satisfying the stakeholder, students and also other parties will be getting attractive to the web application whereby interactive and user friendly approach were embedded. Thus, FSKM Repository System (e-Dissertation module) will be the best solution.